MENAKAR EFEKTIVITAS PEMBELAJARAN DARING PADA MASA PANDEMI COVID- 19 - Yosep Belen Keban (STP Reinha Larantuka, 2021)
The covid-19 pandemic has had such a great influence in various sectors of life and one of the sectors that has felt the impact of this pandemic is the world of education. The online learning from home policy is a strategy to control the transmission of covid-19. This policy is considered very well done to break the chain of transmission of covid-19 in the country. The Learning From Home (BDR) policy forces schools or universities in the country to switch to the world of digital technology so that the learning process runs effectively. The use of technological tools in this situation is a necessity because the world is currently in the 4.0 revolution. Thus, the online method is the most appropriate alternative in the teaching and learning process in this pandemic situation. The application of online learning during this pandemic in the country is certainly not carried out optimally because various obstacles or problems have been found. Problems or obstacles such as internet network problems, data quotas, lack of learning media, weak teacher supervision, teachers who are not technology literate, weak parental supervision in children's learning and so on. This condition is a real problem that occurs in the application of the online learning model. This article will reveal how effective online learning is during the covid-19 pandemic. Pandemi covid-19 telah memberikan pengaruh yang begitu besar dalam aneka sektor kehidupan dan salah satu sektor yang merasakan dampak dari pandemi ini adalah dunia pendidikan. Kebijakan belajar dari rumah (learning from home) secara daring merupakan sebuah strategi pengendalian penularan covid-19. Kebijakan tersebut dinilai sangat baik dilakukan untuk memutus mata rantai penularan covid-19 di tanah air yang semakin mengganas. Kebijakan Belajar Dari Rumah (BDR) tersebut memaksa sekolah-sekolah atau Perguruan Tinggi di tanah air untuk beralih ke dunia teknologi digital agar proses pembelajaran berjalan efektif. Penggunaan alat teknologi dalam situasi ini merupakan sebuah keniscayaan sebab dunia saat ini berada pada revolusi 4.0. Dengan demikian, maka metode daring merupakan alternatif paling tepat dalam proses belajar mengajar pada situasi pandemi ini. Penerapan pembelajaran daring pada masa pandemi ini di tanah air tentu dijalankan belum secara maksimal sebab ditemukan aneka hambatan atau persoalan yang terjadi. Persoalan atau hambatan seperti masalah jaringan internet, kuota data, tidak adanya media pembelajaran, lemahnya pengawasan guru, guru tidak melek teknologi, lemahnya pengawasan orang tua dalam belajar anak dan lain sebagainya. Kondisi tersebut merupakan masalah riil yang terjadi dalam penerapan model pembelajaran daring. Tulisan ini akan mengungkap bagaimana efektivitas pembelajaran daring pada masa pandemi covid-19.